The Element of "Injustice" in The Process of Executing The Auction of Collateral Items From The Murabaha Financing Contract at Shariah Commercial Bank - Cucu Solihah; Dhody Ananta Rivandi Widjajaatmadja; Uus Ahmad Husaeni (Justicia Islamica, 2019)
The provision of Islamic banks' facilities to their customers is practically still applied as collateral, as a form of trust that binds both parties until a contract ends. However, if the customer fails to pay, the opportunity to carry out the collateral may be carried out by the bank as a solution; the last is the customers' obligation that cannot be fulfilled. The bank, as an economic institution, basically does not want to suffer losses. This study aims to analyze the element of ignorance at the auction of Murabaha contract items. The research method uses a normative juridical approach with analytical descriptive data analysis. The findings of this study are that the practice of the execution of collateral still contains the element of death, this can be seen from collateral items that will be auctioned from the beginning of the contract, the value is higher than the facility received by the customer, and sometimes does not involve the customer to determine prices selling collateral, it is not uncommon for the owner of the collateral not to be informed of the execution of the guarantee so that the bank sells collateral at a price not following the wishes of the customer.Pemberian fasilitas yang diberikan bank syariah kepada nasabahnya secara praktik masih diterapkan barang jaminan, sebagai bentuk kepercayaan yang mengikat kedua belah pihak sampai suatu akad berakhir, namun dalam hal nasabah gagal bayar peluang untuk melaksanakan eksekusi atas barang jaminan mungkin saja dilakukan oleh pihak bank, sebagai solusi terakhir atas kewajiban nasabah yang tidak dapat ditunaikan dan pihak bank sebagai lembaga ekonomi pada dasarnya tidak mau mengalami kerugian. Tujuan dari penelitian ini yaitu untuk menganalisis unsur kezaliman pada lelang barang jaminan akad murabahah. Metode penelitian menggunakan pendekatan yuridis normatif dengan analisis data deskriptif analitis. Temuan penelitian ini yaitu praktik proses eksekusi atas barang jaminan masih mengandung unsur kedholiman, hal ini terlihat dari barang jaminan yang akan di lelang sejak awal akad, nilainya lebih tinggi dari fasilitas yang diterima nasabah, dan dalam proses lelang terkadang tidak melibatkan pihak nasabah untuk menentukan harga jual atas barang jaminan, bahkan tidak jarang pihak pemilik barang jaminan tidak diberi tahu pelaksanaan proses eksekusi jaminan itu, sehingga pihak bank menjual barang jaminan dengan harga yang tidak sesuai dengan keinginan pihak nasabah.